Penerapan Model Pembelajaran Kooperatif Tipe NHT Menggunakan Media Kartu Uno IPA untuk Meningkatkan Hasil Belajar Siswa di Kelas VII5 SMP Negeri 2 Lingsar - Zulmiswal Suherli; Abdul Wahab; Resti Fitriati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to improve the science learning outcomes of class VII5 students of SMP Negeri 2 Lingsar by implementing the NHT type cooperative learning model using the Uno Science card media. This study was carried out in two cycles, where students' science learning outcomes increased from cycle I to cycle II. In cycle I, the average class score was 77.50 with classical completeness of 78.95%, while the average score of student learning activities was 18.2 which was in the active category. In cycle II, the average score was 82.23 with classical completeness of 94.73%, while the average score of student learning activities was 22.7 which was in the very active category. This study shows that student learning outcomes and learning activities have increased and achieved success indicators in cycle II. Thus, the application of the NHT type cooperative learning model using the Uno Science card media can improve the learning outcomes of class VII5 students of SMP Negeri 2 Lingsar in the 2024/2025 academic year